The importance of grammar in English language teaching - Adash Eshankulovna Rustamova; Bakhriddinova Farangiz Bobir qizi (Zien Journals, 2023)
In this article, you will be informed about the role of grammar in English language. Hope, if you have some hesitation in the question whether learning grammar is essential or not, you will find the solution to this question in our article.
Keywords: correction; rules; language